INTRAMUSCULAR OXYTOCIN SHOULD IT BE INJECTED AS ROUTINE TO CONTROL POSTPARTUM HEMORRHAGE? - Mooshkbid Haghighi, M; Kamjoo, A; Pedooim, P; Kamali, P (Iran University of Medical Sciences, 2001)
Background: Postpartum hemorrhage considered to be one of the most important cause of women mortality in developing countries. Usage of oxytocin is one of the outstanding success in medicine but it should not be taken for granted and should be used only if it is necessary and not as routine.   Objective: To determine the amount of postpartum hemorrhage on the absence of IM injection of oxytocin.   Design: This was a randomized controlled clinical trial. Control group received to units of oxytocin after completion of second of labor which was the hospital's routine but the trial group did not get any drugs. The amount of blood for first one hour after completion of 3rd stage, 23 hours after that, and altogether 24 hours after labor were compared in two groups.   Sample: 120 full term women with singleton pregnancy who had no problem were randomly assigned to one of the trial (with out oxytocin) or control (with oxytocin) group (60 in each group).   Results: There was no significant difference between the two groups considering amount of post partum hemorrhage at 4th stage of labor, 23 hours after that and altogether 24 hours after delivery.   Discussion: The usage of oxytocin is not recommended as routine at least for those who have normal pregnancy and delivery. But further researches are necessary to make us able to make definite decision.